2014
DOI: 10.1159/000368312
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Expression Discrepancy between Primary and Metastatic Breast Cancer Lesions

Abstract: SummaryBackground: Recent studies have shown that the expression status of hormone receptors and human epidermal growth factor receptor 2 (HER2) in breast cancer may change during disease progression. The aim of this study was to determine and compare the estrogen receptor (ER), progesterone receptor (PR), and HER2 expression status in primary breast cancer and metastatic lesions. Methods: 58 patients with registered biopsy reports or available samples of the primary tumor and distant metastases were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Figure 3 is an example of one of the patients that switched from endocrine therapy to chemotherapy after a liver biopsy. These results are consistent with pathology studies where receptor discordance was found in approximately 15% of metastatic lesions compared to primary lesions (26, 27). In another case report study, temporal heterogeneity was seen in serial FES scans in a patient who was imaged at four time points: prior to initiation of endocrine therapy; after response to endocrine therapy; at subsequent disease progression on endocrine therapy; and at disease progression on chemotherapy (Figure 4).…”
Section: Fes Can Be Used To Identify Tumor Heterogeneitysupporting
confidence: 91%
“…Figure 3 is an example of one of the patients that switched from endocrine therapy to chemotherapy after a liver biopsy. These results are consistent with pathology studies where receptor discordance was found in approximately 15% of metastatic lesions compared to primary lesions (26, 27). In another case report study, temporal heterogeneity was seen in serial FES scans in a patient who was imaged at four time points: prior to initiation of endocrine therapy; after response to endocrine therapy; at subsequent disease progression on endocrine therapy; and at disease progression on chemotherapy (Figure 4).…”
Section: Fes Can Be Used To Identify Tumor Heterogeneitysupporting
confidence: 91%
“…Better survival was demonstrated in patients with either primary or metastatic disease ER positivity compared to those with ER-negative disease. 14 , 16 , 17 However, survival advantage was not significant in all studies, 18 which may reflect on study size or duration of follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Current methods for the determination of HER2 status, immunohistochemistry, and fluorescence in situ hybridization are invasive, requiring biopsy samples [6]. Furthermore, these techniques are of limited use for dealing with the heterogeneous nature of HER2 expression in the primary tumor and the significant discordance in HER2 expression in primary tumor and metastases as well as among metastases in an individual patient [7, 8]. In contrast, molecular imaging techniques such as positron emission tomography (PET) are noninvasive and can provide global status of HER2 in real time [9].…”
Section: Introductionmentioning
confidence: 99%